Storming the tulips - Sanders, Ronald; Voyles, Hannie J. (Saint Louis, Mo. : Stonebrook Pub., 2011)
Presents the stories of twenty students who attended the First Montessori School in Amsterdam during the Holocaust, discussing the hardships and tragedies the children faced when friends and family members disappeared, some were sent to death camps, some joined the Nazi youth, and some struggled to find food.
Poem: The children -- Holland or the Netherlands -- The Nazi storm -- Herding the Jews -- Poem: Razzia in Amsterdam -- Timeline of restrictions -- Sifting the children, shuffling the schools -- My father, Jan van Dam -- The 1st Montessori School connection -- The exodus begins -- The suicide pact: The Pinkhof family -- Saved by my dog / David van Huiden -- From Nazi darling to starving prisoner / Inge Preuss -- Even my baby sister / Bram Asscher -- Stuffed in a cattle car / Esther Santcroos -- From the mouth of hell / Jet Edersheim -- A bullet through my knee / Anny Morpurgo -- Begging for food / Cora Landzaat -- Sent off to strangers / Roos Groenman -- Shuffled around the Netherlands / Sal Groenman -- My parents imprisoned / Floris Haak -- Saving Jewish children / Elly de Zwart -- Bad boy / Fred Huijser -- Nazi youth member / Jan Ponne -- A German hiding Jews / Karin de Jongh -- From Communists to resistance workers / Rudi Leikies -- Picking pockets of the dead / Hannie J. Ostendorf Voyles -- Poem: This Was the Day -- Hiding Jewish children / Jeanne Lindeman -- Driven to the attic : the principal / Wim F. Eijgenstein -- Traversing the Netherlands / Sini Broerse -- RAF pilot / Daniel Sajet -- Resistance fighters / Sape and Bram Kuiper -- Killed after the war ended / Willem Zeeman -- The search into our past -- Rollbook of the dead.
Translation from Dutch of In verband met de vermindering van het aantal kinderen--.
Includes register of names of students of the 1st Montessori School, Amsterdam, who died in the Holocaust (p. 149-154).
Includes bibliographical references (p. 164).
Keywords: Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam -- Personal narratives; Jewish children in the Holocaust -- Netherlands -- Amsterdam -- Biography